2016
DOI: 10.1016/j.mce.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead box O member FOXO1 regulates the majority of follicle-stimulating hormone responsive genes in ovarian granulosa cells

Abstract: FSH promotes maturation of ovarian follicles. One pathway activated by FSH in granulosa cells (GCs) is phosphatidylinositol-3 kinase/AKT. The AKT target FOXO1 is reported to function primarily as a repressor of FSH genes, including Ccnd2 and Inha. Based on its broad functions in other tissues, we hypothesized that FOXO1 may regulate many more GC genes. We transduced GCs with empty adenovirus or constitutively active FOXO1 followed by treatment with FSH for 24 hours, and conducted RNA deep sequencing. Results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 72 publications
3
34
0
Order By: Relevance
“…By these means, FOXO1 can no longer stimulate the expression of autophagy-related genes [35]. FOXO1 is key to the differentiating action of FSH, at least in granulosa cells and, quite unexpectedly, a recent genome-wide analysis revealed that most FSH-responsive genes had FOXO1-binding sites in their promoter (60% of identified genes), and not CREB-binding elements (CRE), as anticipated [36]. While FOXO1 is constitutively nuclear and bound to DNA, where, for example, it inhibits the expression of proliferation genes such as Cyclin D2 [37], these data suggest that the role of FSH would be to counteract the general action of this transcription factor.…”
Section: Fsh-induced Signaling Networkmentioning
confidence: 69%
“…By these means, FOXO1 can no longer stimulate the expression of autophagy-related genes [35]. FOXO1 is key to the differentiating action of FSH, at least in granulosa cells and, quite unexpectedly, a recent genome-wide analysis revealed that most FSH-responsive genes had FOXO1-binding sites in their promoter (60% of identified genes), and not CREB-binding elements (CRE), as anticipated [36]. While FOXO1 is constitutively nuclear and bound to DNA, where, for example, it inhibits the expression of proliferation genes such as Cyclin D2 [37], these data suggest that the role of FSH would be to counteract the general action of this transcription factor.…”
Section: Fsh-induced Signaling Networkmentioning
confidence: 69%
“…Indeed, in a recent report, DUSP27 blocked ERK but not MEK phosphorylation in a rat luteal cell line in response to prolactin treatment (40). However, DUSP27 is not expressed in rat GCs based on both microarray (41) and RNA sequencing (22) results. Although 61 DUSPs have been identified (as reviewed in Ref.…”
Section: Bothmentioning
confidence: 98%
“…The tyrosine phosphatase SRC homology 2 domain-containing tyrosine phosphatase (SHP2) is also required for RTK signaling into MEK/ ERK and is generally believed to contribute to the activation of RAS (26 -28). We determined whether SHP2 activity was required for the phosphorylation of MEK(Ser 217 /Ser 221 ) by pretreating GCs without or with NSC 87877, a compound that selectively inhibits SHP1 (which is not expressed in rat GCs based on RNA sequencing results (22)) and SHP2 (29 . A, GCs were treated for 15 min without (DMSO) or with 250 nM AG1478, an EGFR kinase inhibitor, followed by treatment without (veh) or with 50 ng/ml FSH for 15 min.…”
Section: Bothmentioning
confidence: 99%
See 1 more Smart Citation
“…The forkhead box (FOXO) family of transcription factors is implicated in longevity and aging-related processes, including cell cycle arrest, oxidative stress, DNA repair, apoptosis, and autophagy [47]. Foxo1 is a master regulator of FSH-target genes in granulosa cells [48]. It is highly expressed in growing follicles, repressed during luteinization, and induced in atretic and developing cystic follicles of middle-age acyclic rats at persistent estrous [49].…”
Section: Transcriptional Control In the Aged Multiparous Ovarymentioning
confidence: 99%